Benchmark results for testing adaptive finite element eigenvalue procedures - Giani, Stefano; Grubišić, Luka; Ovall, Jeffrey (Elsevier, 2011)
A discontinuous Galerkin method, with hp-adaptivity based on the approximate solution of appropriate dual problems, is employed for highly-accurate eigenvalue computations on a collection of benchmark examples. After demonstrating the effectivity of our computed error estimates on a few well-studied examples, we present results for several examples in which the coefficients of the partial-differential operators are discontinuous. The problems considered here are put forward as benchmarks upon which other adaptive methods for computing eigenvalues may be tested, with results compared to our own.